News Reporting: Substitution of Functions - Lena N. Pavlova; Nikita A. Argylov (RUDN Journal of Studies in Literature and Journalism, 2021)
The issue of journalistic functions fulfillment by the modern mass media is considered. The authors examined a number of news reports in socio-political online media and found some cases where the classic functions of journalism such as informing and controlling were substituted by PR functions. The content analysis revealed an alarmingly large number of pseudo journalistic reports, which mainly aimed to create and maintain a positive image. The reason why journalism is losing its value is the lack of professionals representing the public interest. The analysis shown a high number of publications, based on (practically unchanged) press releases, that is common to a number of media and clearly illustrates the unprofessionalism of the authors of pseudo news. The regional media have to monetize its activity, so the matter of finance wins over the matter of beliefs. However, the media and, in particular, journalism is quickly losing public credibility. In general, we are witnessing the undermining of classical journalistic creativity and the merging of this concept with other wider categories of public relations.